1/3[1/3(1/3+1/3x)]=1/3
Răspunsuri la întrebare
Răspuns de
6
1/3×(1/3+1/3x) =1/3×3
1/3×(1/3+1/3x)=1
1/3+1/3x=1×3
1/3+1/3x=3
1/3x=3-1/3 amplificam pe 3 cu 3
1/3x=(9-1)/3
1/3x=8/3
x=8/3×3
x=8
1/3×(1/3+1/3x)=1
1/3+1/3x=1×3
1/3+1/3x=3
1/3x=3-1/3 amplificam pe 3 cu 3
1/3x=(9-1)/3
1/3x=8/3
x=8/3×3
x=8
Alte întrebări interesante
Limba rusă,
8 ani în urmă
Matematică,
8 ani în urmă
Limba română,
8 ani în urmă
Limba română,
9 ani în urmă
Engleza,
9 ani în urmă
Matematică,
9 ani în urmă
Matematică,
9 ani în urmă